High SARS-CoV-2 Infection Rates Among Special Forces Police Units During the Early Phase of the COVID-19 Pandemic in Ecuador - Ortiz-Prado, Esteban; Andrade, Felipe; Vasconez, Eduardo; Escobar-Espinosa, Cristina; Vallejo-Janeta, Alexander Paolo; Freire-Paspuel, Byron; Coronel, Barbara; Galvis, Heberson; Morales-Jadan, Diana; Rivera-Olivero, Ismar A.; Lozada, Tannya; Henriquez-Trujillo, Aquiles R.; et al. (Frontiers in Medicine, 2022)
Background. The coronavirus disease 2019 (COVID-19) has evolved into the current worldwide pandemic. This resulted in unprecedented challenges for public health systems worldwide that were faced with dramatic population lockdowns. However, police officers were required to continue their labor as essential personnel during this critical time, which resulted in safety concerns as their labor includes personal contact, continuous mobilization and difficulty in maintaining sanitizing measures. Objective. A cross-sectional study was designed to describe the attack rate of SARS-CoV-2 infection among Special Forces Police Officers in Quito, Ecuador in the month of July 2020. Results. 163 community dwelling police officers from elite divisions voluntarily participated and were tested for SARS-CoV-2 infection by RT-qPCR. A total of 20 out of 163 police officers tested positive for SARS-CoV-2, yielding a high attack rate of 12.27%. 10% (2/20) of SARS-CoV-2 positive indivuals were superspreaders with viral loads over 108 copies/mL. 85% of the SARS-CoV-2 positive individuals were asymptomatic and 15% reported mild symptoms related to COVID-19. Conclusions. We found a high SARS-CoV-2 attack rate within the special forces police officers that beyond a high health risk for themselves, their families and coworkers, could trigger a national security issue. Our results point out the need of permanent SARS-CoV-2 testing among asymptomatic essential workers to prevent a worse social collapse that the already caused by COVID-19 pandemic.